Factors associated with fibro-cavernous tuberculosis - Arailym Abilbayeva; Anel Tarabayeva; Akbope Myrkassymova; Amanzhan Abubakirov; Ilsiyar Khaertynova; Eduard Shuralev (National Scientific Medical Center, 2022)
Objective: To identify socio-demographic, clinical and laboratory risk factors associated with fibro-cavernous tuberculosis. Material and methods: Clinical and laboratory data of 184 patients with pulmonary tuberculosis who were treated at the National Scientific Center for Phthisiopulmonology of the Ministry of Healthcare of the Republic of Kazakhstan were analyzed. Specific antibodies to the lipoglycan of M.tuberculosis (MBT) were evaluated in an immunochromatographic assay. To assess the significance of differences in groups, the Pearson Chi-Square test was used. To determine factors associated with the fibro-cavernous tuberculosis, а multiple binary logistic regression analysis was carried out. Results: Multivariate logistic regression analysis showed that low BMI (OR=5,719, 95% CI: 2,049-15,965, p=0,001), TB recurrence (OR=3.374, 95% CI: 1,191-9,561, p=0,022), and a negative specific production of antibodies to lipoglycan of M.tuberculosis (MBT) (OR=0,354, 95% CI: 0,126-0,995, p=0,049) were significantly associated with fibro-cavernous tuberculosis. Conclusion: Weight deficiency, high antibodies levels and TB relapse are factors associated with fibro-cavernous tuberculosis.